2009
DOI: 10.4049/jimmunol.0900668
|View full text |Cite
|
Sign up to set email alerts
|

Critical Roles of Translationally Controlled Tumor Protein in the Homeostasis and TCR-Mediated Proliferation of Peripheral T Cells

Abstract: Translationally controlled tumor protein (TCTP) is expressed throughout T cell development and prominently induced following T cell activation. However, its function(s) during these processes is unclear. Here, we demonstrated that conditional deletion of TCTP before the β selection checkpoint resulted into a partial block of thymocyte development at the double-negative (DN) 3 stage. Deletion of TCTP in the double-positive (DP) stage did not cause any significant phenotype in the thymus except a slight increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Traditionally, TCTP is released from a series of immune cells (basophils [15], eosinophils [16] and thymus [17]) and some types of cancer cells (prostate cancer [18]). To verify whether TCTP could be secreted from CRC cells, TCTP concentration was determined by ELISA in the culture supernatant of six CRC cell lines cultured under normal conditions (10%FBS and normoxia), in serum-free medium (1%FBS and normoxia), in hypoxic (10%FBS and 1%O 2 ) conditions and in serum-free medium plus hypoxia (1%FBS and 1%O 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, TCTP is released from a series of immune cells (basophils [15], eosinophils [16] and thymus [17]) and some types of cancer cells (prostate cancer [18]). To verify whether TCTP could be secreted from CRC cells, TCTP concentration was determined by ELISA in the culture supernatant of six CRC cell lines cultured under normal conditions (10%FBS and normoxia), in serum-free medium (1%FBS and normoxia), in hypoxic (10%FBS and 1%O 2 ) conditions and in serum-free medium plus hypoxia (1%FBS and 1%O 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of TUNEL-positive cells in embryos at day 5.5 showed no difference between wild-type and TCTP-deficient mice 21 . TCTP deletion in T cells caused no reduction in thymocyte numbers 25 . In addition, an inverse relationship between TCTP expression and growth rate was found with an epithelial cell line 26 .…”
Section: Introductionmentioning
confidence: 94%
“…In 2009 two papers showed the importance of TCTP in preventing apoptotic cell death for the maintenance and development of T-cells. Using conditional TCTP knockout mouse models, Wu and colleagues [49] demonstrated that TCTP is essential for the viability of mature peripheral T-cells. Xiong et al [50] reported that IL-2 promotes the survival of regulatory T-cells through stimulation of TCTP expression.…”
Section: + -Atpasementioning
confidence: 99%